Undergraduate research in schools offering library and information science courses in Metro Manila (1992-1997) - Arellano, Christine B.; Dizon, Leticia B. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1998)
This study is undertaken to show the research patterns in the field of library and information science in the undergraduate level. The general objectives of the study are: to know the trends in Library and Information Science (LIS) research in thirteen undergraduate LIS schools in Metro Manila; to draw suggestions for further studies in the area; and to make recommendations on evaluating and developing research in the LIS field. The specific objectives of this study are: to know what topics or areas are usually researched on or evaluated by LIS students of LIS schools in Metro Manila; to find out if there is any shift in terms of research topic or area of study in the field of LIS from 1992 to 1997; to know what method of research is predominantly used; to find out if there is any significant change in the trend of the method employed in conducting the research; to know the possible relationships between the areas of research and the gender of the researchers; and to know the possible relationships between the methodology used and the gender of the researcher.
Data gathering was done through content analysis using a worksheet. Results were tabulated to facilitate data analysis and interpretation.
The study shows, based on statistical tests, that there is no correlation between gender of researcher and subject of research and also there is no correlation between gender of the researcher and the methodology employed.
The study revealed that out of the 13 LIS schools in Metro Manila, only the Institute of Library Science in UP Diliman required its students to submit undergraduate theses, the rest simply asked for book policies (University of Santo Tomas) and term papers/special projects (Arellano University, Centro Escolar University, Far Eastern University, Manuel L. Quezon University, National Teacher's College, Philippine Normal University, Philippine Women's University, University of the East and University of Manila). The ranking in terms of number of research produced and the dominant area of research conducted per year from 1992 to 1997 are as follows: (1996) reference and information services, (1994) user studies, (1997) librarians/library profession, (1993) reference and information services and user studies, and (1992) public library and resource sharing. The commonly studied area of research is user studies. In terms of research methods used, majority of the researchers used the descriptive survey research method; majority of the undergraduate researches in the LIS field were conducted by females. Most of the male researchers used the descriptive survey research method while female researchers used the survey research method; both male and female researchers focused on user studies. In terms of areas of research, user studies were mostly used. In terms of research methods used, descriptive survey research method was predominantly used from 1992 to 1997.There are other areas of research that remain unexplored which are of equal importance to the rest.
It is recommended that studies should be conducted focusing on these unexplored areas. The library's collection development should be enhanced. Furthermore, undergraduate theses should be added to the curriculum of those schools which do not require them to prepare the students to become good researchers and to help enrich the literature of the field. For the school which requires undergraduate theses, its course on research should be enhanced in preparation for the thesis-writing of the students. Research curriculum and training should be developed further. Moreover, advisers should give suggestions to enrich the literature of Philippine librarianship.
Computer print out.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Dissertations, Academic--Philippines--Manila Metropolitan Area; Library schools--Philippines--Manila Metropolitan Area